Baseline Predictors of Visual Acuity Outcome in Patients with Wet Age-Related Macular Degeneration. (26th February 2018) - Zhang, Xinyuan; Lai, Timothy Y. Y.
Abstract : Age-related macular degeneration (AMD) is one of the leading causes of severe vision loss in people over 60 years. Wet AMD (wAMD) causes more severe visual acuity (VA) loss compared with the dry form due to formation of choroidal neovascularization (CNV). Antivascular endothelial growth factor (anti-VEGF) agents such as ranibizumab and aflibercept are now the standard of care treatment for wAMD. Unfortunately, up to a quarter of anti-VEGF-treated wAMD patients might not fully benefit from intravitreal injections and CNV activity may not respond to the treatment and these patients are called anti-VEGF nonresponders. This article aims to discuss the baseline factors associated with VA outcome such as age, initial VA, lesion types, disease duration, optical coherence tomography (OCT) features, fundus autofluorescence findings, and the presence of particular genotype risk alleles in patients with wAMD. Recommendations are provided regarding when to consider discontinuation of therapy because of either success or futility. Understanding the predictive factors associated with VA outcome and treatment frequency response to anti-VEGF therapy may help retina specialists to manage patients' expectations and guide treatment decisions from the beginning of treatment on the basis of "personalized medicine."